First Principle Modelling of Interplay between Langmuir Probes and Plasma Turbulence. Issue 6 (12th July 2016) - Futtersack, R.; Colin, C.; Tamain, P.; Ciraolo, G.; Ghendrih, Ph.; Marandet, Y.; Schwander, F.; Serre, E.
Abstract: The interplay between Langmuir probes (LP) and Scrape‐Off‐Layer plasma turbulence is numerically investigated with the TOKAM2D and TOKAM3X fluid codes. The LP is modelled by biasing a part of the target plates surface; we then study its impact on the turbulent transport 1) in presence of electron temperature fluctuations and 2) with a complete description of the parallel dynamics. We find that a biased probe can disturb local plasma parameters as well as turbulent transport in its vicinity, by polarizing the connected flux tube and thus driving a strong ExB vortex. Moreover, electron temperature fluctuations are found to account significantly those of floating potential, but with a limited impact on flux measurements depending on the probe's exact geometry. The 3D study of the problem shows the attenuation, but the persistency, of these perturbations induced by the presence of the LP. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)